Education Through Athletics - Erianne A. Weight; Matt R. Huml (Journal of Intercollegiate Sport, 2016)
Fundamental to the union of athletics and the academy is an underlying theoretical premise of education through athletics. Despite an organizational union of varsity athletics and American higher education, athletics is commonly viewed as extracurricular, tangential, or a detractor from the educational mission of the academy, and athletics-centric curricula have historically not been viewed as worthy of academic credit despite documented educational benefits. Through survey of a stratifiedrandom sample of National Collegiate Athletics Association (NCAA) Division I, II, and III athletic academic advisors (n = 240), this exploratory study examined the prevalence, design, and institutional perceptions of classes offered exclusively for varsity athletes. Results indicate roughly 1/3 of sample schools facilitate athletecentric academic opportunities, with the majority of courses being 1st semester transition, physical education, or leadership courses. Academic opportunities for athletes were greatest in western, public, and Division I institutions.